(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The COVID-19 pandemic has challenged every aspect of one’s life, especially in the education setting. Educators are confronted with various challenges to be creative in delivering instructions despite several limitations caused by the pandemic. Thus, the gamification approach embedded in modular instruction in education is integrated by making each lesson interactive through progress trackers and badges in every game-based related activities to the lessons that have been used to sustain and enhance students’ motivation and learning engagement in the modular setup through a conducted Randomized Block Research Design. In this paper, the objectives were to (1) determine the profile of the students in terms of the type of institution they belong to, sex, age, degree program, and the course they were enrolled in the 2nd Semester A.Y. 2019-2020. Second (2) it determined the assessment of the module in terms of three areas such as format, content, and gamified features of the module. It also (3) tested the significant difference of the mean assessment of the module when grouped according to profile so that the educators will know how to contextualize the gamified module for its possible improvement. Notwithstanding, the concluded integration of the aspects of the module in terms of the format, content, and gamified features were all highly received positively by the 279 purposive-conveniently sampled respondents who participated from a local college in Laguna and a state university in Manila from the College of Education. The format, content, and gamified features of the module were all with high regards, however, with some notable remarks including the module cover, color, and template, insufficiency of the illustrative examples, and the improvement of progress tracker, badges, incentive system, and the game-based activities related to the lessons. Also, there is no statistical difference in the perceived use of the gamified module in many areas implied that there is a consistent presentation of the three areas whether in the different institution, age brackets, sex orientation, year levels, degree program, and course taken except those of the format since education courses were oriented to instructional materials standards gave them the ability to assess it more comprehensively. Another significant assessment was traced to content and gamified features of the males since males are more exposed to games perhaps lead them the expectations to a more similar approach to the games they were exposed to. The study recommended that though they find the gamified module as an innovative tool and unique way of learning amid the pandemic, improvements in terms of the badges, the activities presented in the module, and some additional features of the real game such as real and more creative badges, leaderboards and incentive system. Indeed, the paper moves forward the field of knowledge through the enhanced gamified module of several courses that can be a design guide of other disciplines.